The role of the role of neuroscience in defining ‘brain death’: a philosophical approach - Falla de Güich, Myriam Patricia (2016)
This paper intends to approach to the notion of ‘brain death’ as a paradigm used to determine ‘clinical death’, not as the death of the brain and the survival of the body, but rather as the cessation of all vital functions, i.e. death per se. This notion of ‘brain death’ will be analyzed based on what neurosciences can contribute today regarding the nature and complexity of the brain, and simultaneously, breaking new grounds when attempting to give an answer to this matter.